2022
DOI: 10.1155/2022/4655939
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Circ_0109046 Regulating Mir-338-3p on the Malignant Behavior of A2780 Cells

Abstract: Objective. The objective is to explore the action and mechanism of circ_0109046 on the malignant phenotypes of ovarian cancer cells. Methods. Circ_0109046 and miR-338-3p expression were detected by quantitative real-time polymerase chain reaction (qRT-PCR). In vitro assays were conducted to investigate the action of circ_0109046 and miR-338-3p on ovarian cancer cell growth and metastasis. Western blotting was utilized to investigate the contents of apoptosis-related markers. The binding between circ_0109046 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%